Vibration Diagnosis and Prognostics of Turn-milling Operations using HSS and Carbide End Mill Cutters. (2016) - Vikram, K. Arun; Ratnam, Ch.; Narayana, K. Sankar
Abstract: Vibrations are the leading phenomenon in analyzing surface finish and machine condition. The present work focuses on effect of machining parameters on Surface Roughness (Ra) and Tool Vibrations (VIB) in manufacturing operational methods like tangential and orthogonal turn-milling processes. Single cut machining on A-axis of CNC Vertical Milling centre using HSS and carbide end mill cutters are adopted. Process parameters like cutter (tool) speed, feed rate and depth of cut with constant rotation of workpiece on A-axis are chosen while machining Extruded brass material under dry condition. Statically design experiments based on Taguchi's philosophy of Orthogonal Array (OA) is adopted for experimentation. Online capturing of Acousto-optic emissions (AOE) of tool shank vibrations is done using Laser Doppler Vibrometer (LDV) and is analyzed using VibSoft analyzer. Peak vibrations displacements of the cutting tool shanks are identified using Fast Fourier Transforms (FFT) over time domain signals and are used for vibration diagnosis and prognostics as a measure of machine tool condition monitoring, Failure Mode and Effective Analysis (FMECA) based on ISO standards is used for vibration prognostics.